Integrated and sustainable agroecological production for medicinal plants: a proposal based on strategic management (Sustainability in Debate, 2022)
A management plan based on Integrated and Sustainable Agroecological Production (Pais) technology for the cultivation of medicinal plants, through a case study. The Swot-AHP technique was adopted to evaluateproblems to agroecological cultivation, indicating stages of the implementation work, before the physical structuring of the project, integrated with a participative social action with employees of the institution who revealed the use of 64 medicinal plants, highlighting boldo, lemongrass, and lemon balm, while 174 plant species were identified in official Brazilian documents. The lack of electricity and funding delays by funders are the most significant problems, while the space for work and gardening courses are the best potential. The integration of these data has proposed the implementation of teams for fundraising and project implementation, based on a list of medicinal species to compose the future structure made with Pais social technology.